2023
DOI: 10.3389/fonc.2023.1077309
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a new prognostic risk model of MAPK pathway-related molecules in kidney renal clear cell carcinoma based on genomes and transcriptomes analysis

Abstract: PurposeThe mitogen-activated protein kinase (MAPK) signaling pathway is often studied in oncology as the most easily mentioned signaling pathway. This study aims to establish a new prognostic risk model of MAPK pathway related molecules in kidney renal clear cell carcinoma (KIRC) based on genome and transcriptome analysis.MethodsIn our study, RNA-seq data were acquired from the KIRC dataset of The Cancer Genome Atlas (TCGA) database. MAPK signaling pathway-related genes were obtained from the gene enrichment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Currently, research on disul dptosis is still in its early stages and mainly focuses on a few types of tumors. For instance, studies have found that multiple disul dptosis-related genes, such as LRPPRC, OXSM, GYS1, and SLC7A11, are associated with prognosis in patients with renal clear cell carcinoma (Zhang D et al, 2023). Additionally, research by Zhang et al suggests that disul dptosis-related genes, such as KIF20A, G6PD, SLC7A11, and SLC2A1, play a role in the development of liver cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, research on disul dptosis is still in its early stages and mainly focuses on a few types of tumors. For instance, studies have found that multiple disul dptosis-related genes, such as LRPPRC, OXSM, GYS1, and SLC7A11, are associated with prognosis in patients with renal clear cell carcinoma (Zhang D et al, 2023). Additionally, research by Zhang et al suggests that disul dptosis-related genes, such as KIF20A, G6PD, SLC7A11, and SLC2A1, play a role in the development of liver cancer .…”
Section: Introductionmentioning
confidence: 99%